Algoritma Apriori Sebagai Solusi Kontrol Persediaan Suku Cadang Mobil PT. Buanasakti Aneka Motor Jakarta - Normah Normah; Bakhtiar Rifai; Pita Sari (Paradigma, 2020)
PT. BuanaSakti Aneka Motor is one of the car distributor agents located at warung buncit raya street No. 109 Duren Tiga, South Jakarta. Everyday the data piles is increase more and longer. PT. BuanaSakti Aneka Motor sometimes has difficulty to knowing how many spare parts occur in one transaction, so data or new stock information is difficult to find sometimes experiencing errors. To find out which products have the most sales and how they relate to one another, a priori algorithm method and the help of Rapidminer Tools are needed to produce associative rules. From the results of the discussion and analysis of the data it can be concluded that the application of a priori algorithm in determining the combination of itemset with a minimum support of 25% and a minimum of 60% confidence found 2 association rules, where the highest value of support and confidence is a radiator with a minimum stop lamp support of 26.92% while the minimum confidence is 64.65% and the oil filter with the minimum stop light support is 35.32% while the minimum confidence is 61.58%.